PENGEMBANGAN KARIR ANGGOTA KEPOLISIAN DALAM MENINGKATKAN KINERJA DI SATUAN RESERSE KRIMINAL POLRES TOMOHON - Mantiri, Jeane; Sewow, Miesyel; Wawointana, Thelma (Gapenas Publisher, 2025)
This research aims to analyze career development among police officers in improving performance quality at the Criminal Investigation Unit (Satreskrim) of the Tomohon Police Department. The study used a qualitative descriptive method with data collected through interviews, observations, and documentation. The results show that career development efforts remain suboptimal due to limited training quotas, lack of developmental education, and ineffective promotion processes. It is recommended that training programs be made more relevant and competency-based promotion systems be improved to support optimal performance.